Administrative failure, state capacity, and democratic exclusion: Evidence from Berlin's 2021 election breakdown - Marius Kröper (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2025)
This paper studies the long-run effects of non-strategic administrative failures on voter participation. I exploit a natural experiment from Berlin's 2021 elections, in which hundreds of precincts experienced ballot shortages, multi-hour queues, and unlawful polling closures. Using precinct-level administrative data and a stacked event study design, I show that precincts exposed to administrative failures in the 2021 Berlin election experienced a 1.8 percentage points (2.4%) decline in turnout across three subsequent elections over the next four years. The drop is concentrated in in-person voting and only partially offset by increases in postal participation in subsequent elections. Effects are largest among young voters, welfare recipients, and residents with migration backgrounds. Survey evidence suggests two mechanisms: disrupted civic habit formation and short-term erosion of institutional trust.
urn:nbn:de:bsz:14-qucosa2-1004957
Keywords: D72; H11; H70; R50; 330; State Capacity; Voter Turnout; Voting Costs; Administrative Failure